THE STATUTE OF CHILDREN AND ADOLESCENTS AND THE LEGAL INSTITUTE OF REMISSION (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
ABSTRACT This article proposes to address the alternations between criminal and socio-educational law, with an analysis of constitutional principles, children, adolescents and the execution of socio-educational measures. It concludes with a study of the legal foundations of remission, its nature, conditions and hypotheses in the Statute of the Child and Adolescent. The aim of the study is to analyze the history of children and adolescents in Brazil, discussing the principles of guilt and full protection. It addresses socio-educational measures together with the National Socio-Educational Care System, to demonstrate the relevance of remission to adolescents. The article's methodology is deductive and qualitative. The exploratory bibliographical review provides familiarity with the problem, including sources of public documents on the subject. Positive elements are highlighted regarding the application of remission to adolescents, this modality avoids the negative effects of the judicial procedure. It offers judges a device that is appropriate to the changing nature of life in development. The conclusion is that remission is important because it makes accountability with education possible. It is an institute of a consensual nature, which aims to re-socialize in the form of forgiveness. It favors the psychological, educational and social development of adolescents, since at this stage they do not have the aptitude to make decisions about their conduct.KEYWORDS: Offense. Child and Adolescent. Socio-educational Measure. Remission.